The Influence Of Work Culture And Job Competence On Medical Personnel Performance In Doctor Suyoto Hospital Emergency Department - Pramudya, Dani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The author's aim in this research is to find out how much influence the work culture and job competence have on improving medical personnel performance both partially and simultaneously at Doctor Suyoto Hospital Emergency Department. The method used in this research is a quantitative research method with descriptive and verification methods. The sampling technique used in this research was the Slovin formula, and the data analysis technique used was the linear regression analysis technique using the SPSS version 2 7.0 application. Based on the analysis carried out, it can be concluded that the work culture and job competence can significantly, either individually or collectively, have an influence on performance at Doctor Suyoto Hospital Emergency Department . Based on respondents' perceptions, the work culture and job competence are in the good category. Likewise, the performance variable is included in the good category. Partially there is a strong and significant influence of the work culture in improving performance, likewise job culture has a large and significant influence on performance. Taken together there is a large and significant influence of the work culture and job competence on medical personnel performance at Doctor Suyoto Hospital Emergency Department.